Effect of Phentolamine Mesylate on Reducing The Time of Local AQnesthesia of Soft tissue in Children – A Clinical Study (Journal of Hama University, 2020)
The aim of this study was to evaluate the effectiveness of phentolamine mesylate (PM) on shortening the duration of soft-tissue anesthesia following routine dental procedures. A total of 60 children aged (9-11) years, weighed more than 15 kg and had indication to use inferior alveolar nerve block due to dental treatment. After 30 minutes of anesthesia the studied drug (containing  phentolamine mesylate or sham injection) was injected,  a cartridge of PM for each cartridge of local anesthetic used. After 10 minutes the sensation of soft- tissue of every patient was checked then repeated every 10 minutes until it returned to the normal sensation, and the period of soft tissues anesthesia was recorded for every child. Statistical study was performed using T-test  at a statistical significance of 0,05. SPSS 21,0 software was used to perform the analyses. The phentolamine mesylate has significantly reduced the median of duration of soft-tissue anesthesia in the lip from  187,67 to 77,3  minutes. The phentolamine mesylate was effective  to reverse soft tissue anesthesia in the studied cases.